Spatial and temporal patterns in Neolithic and Bronze Age agriculture in Poland based on the stable carbon and nitrogen isotopic composition of cereal grains - Mueller-Bieniek, A; Nowak, M; Styring, A; Lityńska-Zając, M; Moskal-Del Hoyo, M; Sojka, A; Paszko, B; Tunia, K; Bogaard, A (Elsevier, 2019)
In this study the stable nitrogen (δ15N) and carbon (δ13C) isotopic compositions of carbonized cereal grains from 18 archaeological sites in Poland, dating from the Early Neolithic to the turn of the Bronze Age and the Iron Age, were determined. There were two main aims of this study. The first aim was to test the archaeologically accepted model of a change from intensive ‘horticulture’ in the Early Neolithic in Lesser Poland to more extensive cultivation in the Middle Neolithic, which is expected to be evidenced by decreasing levels of manuring and labour input, reflected especially in a shift to lower cereal grain δ15N values. The second aim was to assess how cereal grain δ13C values reflect crop watering conditions and landscape openness regionally and through time. Despite the limited plant material, the study showed that all cereal plots potentially received some inputs of manure (including household waste), but there seems to be a clear regional difference in the intensity of manuring practice in the Early Neolithic, with greater manure application on plots in southern Poland than in northern Poland. Moreover, cereal plots in southern Poland in the Early Neolithic seem to have been located on soils with higher water retention and/or within denser vegetation than plots in northern Poland. In the Middle Neolithic, however, plots in southern Poland seemed to have expanded into areas with lower water availability or that were more open, supporting the evidence from former archaeological interpretations that agriculture spread into different, usually elevated areas at this time.